USE OF HIGH DOSE RIFAMPICIN FOR THE TREATMENT OF TUBERCULOSIS MENINGITIS PATIENTS: A SYSTEMATIC REVIEW - Riyan Ashori Hidayat, Andhira; Shafira Zulkarnain, Farah; Iqbal Putra Agusti, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Aim: The objective of this study is to summarize and evaluate the use of high-dose rifampicin for the treatment of tuberculosis meningitis.Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2018–2023. Duplicate publications, review articles, and incomplete articles were excluded.Results: Database searches identified a total of 93 articles. Of these, 22 articles passed the screening process and resulted in 12 articles for full-text assessment. The 6 articles did not evaluate the outcome of interest. Hence, we found 6 appropriate studies included in this review.Conclusion: The results suggest that high-dose rifampicin is not associated with the outcomes of tuberculosis meningitis patients. However, further research especially RCTs is recommended to evaluate comprehensive rifampicin regimens for the optimization of tuberculosis meningitis patients.